Insects With Survival Kits for Desiccation Tolerance Under Extreme Water Deficits - Thorat, Leena; Nath, Bimalendu B. (Frontiers in Physiology, 2018)
The year 2002 marked the tercentenary of Antonie van Leeuwenhoek’s discovery of desiccation tolerance in animals. This remarkable phenomenon to sustain ‘life’ in the absence of water can be revived upon return of hydrating conditions. Today, one of the global challenges is coping with climate change-related factors, especially temperature-humidity imbalance. Under such adverse circumstances, desiccation tolerance remains a prime secret of several plants and few animals to escape the hostile consequences of fluctuating hydroperiodicity patterns in their habitats. Among lower animals, insects, in particular, have demonstrated profound mechanisms by virtue of which they thrive under physiological water deficits without compromising on revival and survival upon rehydration. The focus of this review is to compile the enormous research insights on insect desiccation tolerance gathered over the past several decades from numerous laboratories worldwide working on different insect groups. We provide a comparative overview of species-specific behavioural changes, adjustments in physiological biochemistry and cellular and molecular mechanisms as few of the noteworthy desiccation-responsive survival kits in insects. Finally, we highlight the role of insects as potential candidate models in tracking global warming which will form the basis for translational research to mitigate periods of climatic uncertainty predicted for the future.